2022
DOI: 10.1002/adfm.202208966
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Effect of Intrinsic Carbon Defects on Potassium Storage Performance

Abstract: Defects engineering is an attractive strategy to improve the potassium storage performance of carbon anodes. The current studies mainly focus on the introduction of external defects via heteroatom doping, however, the exploration on the effect of intrinsic defects caused by the loss of atoms or distortion in the crystal lattice on potassium storage is still lacking to date. Hence, a series of carbon materials with different intrinsic defect levels are developed via a soft-template assisted method. It is found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 93 publications
(48 citation statements)
references
References 53 publications
0
36
0
Order By: Relevance
“…Wang et al synthesized carbon materials with different intrinsic defects by a template-assisted method and investigated the effect of intrinsic defects on the potassium storage performance. 53 It was found that higher levels of has a stronger attraction to K than N site (Fig. 7d).…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 81%
See 2 more Smart Citations
“…Wang et al synthesized carbon materials with different intrinsic defects by a template-assisted method and investigated the effect of intrinsic defects on the potassium storage performance. 53 It was found that higher levels of has a stronger attraction to K than N site (Fig. 7d).…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 81%
“…Wang et al synthesized carbon materials with different intrinsic defects using a template-assisted method and investigated the effect of intrinsic defects on the potassium storage performance. 53 It was found that higher levels of intrinsic defects were more beneficial to improve the capacitive behavior by providing sufficient potassium adsorption sites. The researchers revealed a strong positive correlation between the level of intrinsic defects and the capacity/capacity retention, while the wettability of the carbon materials increased with the increase of the defect concentration, resulting in the rapid penetration of electrolyte ions.…”
Section: Recent Advances In Carbon Defect Engineering For Mibsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result reveals that the obtained C content by XPS is relatively higher than that in the whole carbon matrix, in accordance with the previously reported works. [ 4 , 5 ] Moreover, the detected O is supposed to improve the wettability of electrode materials and increase the utilization ratio of active surface, [ 10 , 13 ] thus favoring a good rate and capacity. As displayed in Figure 3d–f , the high resolution XPS spectrum of C 1s can be deconvoluted into three peaks at 284.7, 285.6, and 286.4 eV, [ 27 , 28 ] corresponding to sp2 C, sp3 C, and C−O, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Among all the anodes, carbonaceous materials are highly preferable and have been extensively investigated because of their excellent electrical conductivity and chemical stability. [ 9 , 10 , 11 ] Nevertheless, K‐ions with a larger size (1.38 Å for K + versus 0.76 Å for Li + ) can induce more distinct volume variation of the host electrode and sluggish kinetics for solid‐state diffusion during intercalation/de‐intercalation process, [ 12 , 13 , 14 ] eventually leading to serious capacity decay and inferior rate. Defect engineering in carbon matrix has been proven to be an effective strategy to resolve these issues, and simultaneously contributes to breaking through theoretical capacity to a large extent.…”
Section: Introductionmentioning
confidence: 99%